Verwaltungspolitik der Länder im Vergleich - Götz, Alexander (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2012)
In view of a continuous and far reaching modernization of the public administration since the 1980s the study lays its focus on the analysis of effectiveness of reforms with respect to leading political objectives. Due to the dominance of fiscal motives and economic reasons in this period of time the reduction of personnel expenditures by concentrating the organizational structures of public agencies and administrative bodies represents the main interest of the study. To examine the success of these reforms the author compares the reforms that the German states have gone through over this period of time. This is done on the basis of a generated exclusive data set which shows the organizational and personnel structure of the state administration on this level since the early 1990s. The data set allows both displaying long term developments and differentiated aspects in terms of single cases, public tasks, resorts and agency types. Thereby the descriptive examination presents the amount and intensity of change and allows close insights into the strategies and processes of reform policies. The quantitative analysis of the personnel effects demonstrate a significant correlation between the structural reorganization measures and the reduction of personnel staff in the state agencies which indicates the effectiveness of the considered policies. Furthermore, the results suggest that not only the intensity but also the concepts of structural reforms have an affect on the amount and degree of the intended personnel staff reductions. Eventually this leads to the conclusion that the German states still have a significant potential for reducing their administrative costs by concentrating administrative structures.

Angesichts der seit den 1980er Jahren andauernden, sehr umfassenden Modernisierung der öffentlichen Verwaltung richtet sich die Untersuchung auf die Effektivität und Wirksamkeit von Reformen i. S. ihrer politischen Ziele. Da hierbei vor allem fiskalische Motive maßgeblich waren, steht das Bestreben im Mittelpunkt, die Staatsausgaben und den Personaleinsatz durch eine schlankere Behördenorganisation zu reduzieren. Inwieweit dies auf dem Wege struktureller Reorganisationsmaßnahmen erreicht wurde, untersucht die Arbeit für die deutschen Bundesländer auf der Basis einer vergleichenden quantitativen Analyse. Hierfür wurden eigens Daten zur Behörden- und Personalstruktur der letzten 20 Jahre erhoben, anhand derer sich die Verwaltungs- und Personalentwicklung gesamthaft wie auch differenziert nach Ländern, Aufgaben, Ressorts und Behördentypen abbilden und vergleichen lässt. Dabei zeigt die deskriptive Auswertung den Umfang der stattgefundenen Veränderungen auf und lässt Rückschlüsse auf Verlauf und Strategien der Reformpolitiken zu. Die quantitative Wirkungsanalyse wiederum dokumentiert einen nachweisbaren Zusammenhang zwischen strukturellen Organisations- und den damit intendierten Personalveränderungen, bestätigt mithin die Effektivität der Maßnahmen. Dabei wird auch ersichtlich, dass nicht nur die Intensität, sondern auch die Art der Veränderungen, also das organisatorische Konzept der Reformen den Grad und den Umfang des beabsichtigten Stellenabbaus beeinflussen. Hieraus lässt sich im Ergebnis auch ableiten, dass die deutschen Flächenländer im Vergleich noch ein erhebliches Konzentrationspotenzial aufweisen, um über eine Vereinfachung ihrer Behördenorganisation Effizienzpotenziale zu erschließen.
Administrative Policies of the German Bundesländer - A comparative study of structural reforms and their ressource effects
Empirische Untersuchung zu Strukturreformen und ihren Ressourceneffekten
Keywords: Public Sector; Administrative Reform; Verwaltungsreform; Strukturreform; Öffentlicher Sektor; 320 Politikwissenschaft